SPLENECTOMY IN SPORT INJURY OF THE SPLEEN: A CASE REPORT - Rexhep Selmani; Qemal Rushiti; Goran Begovic; Blerdi Ziba; Georgiev, Antonio (Faculty of Physical Education, Sport and Health in Skopje, Republic of Macedonia, 2016)
The spleen is one of the most vascular organs in the body, so any trauma to the spleen can cause fatal injury in just a matter of minutes if not recognized and treated. Among the abdominal injuries on sport activities, one should always consider spleen injuries. In this study we analyze a case of an adult who suffered from splenic laceration, caused from an immediate fall to the ground while playing soccer. He had a severe spleen injury, felt pain in the abdomen, in the left side of the chest and the left side of the arm, accompanied with feeling of dizziness, nausea, vomiting, paleness and dyspnea. After having the results of the abdominal examination, CBC, CT, sonography, a review by a cardiologist, the surgeon decided to perform a splenectomy, which prevented the hemorrhage and the maintained of the hemodynamic stability.
Keywords: spleen injury; contact injury; sport injury; splenectomy